2017
DOI: 10.3201/eid2312.170951
|View full text |Cite
|
Sign up to set email alerts
|

High Abundance and Genetic Variability of Atypical Porcine Pestivirus in Pigs from Europe and Asia

Abstract: Atypical porcine pestivirus (APPV) was recently reported to be associated with neurologic disorders in newborn piglets. Investigations of 1,460 serum samples of apparently healthy pigs from different parts of Europe and Asia demonstrate a geographically wide distribution of genetically highly variable APPV and high APPV genome and antibody detection rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
115
3
8

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 69 publications
(129 citation statements)
references
References 10 publications
3
115
3
8
Order By: Relevance
“…Moreover, it has been reported that detection rates of 2.4% to 22% for APPV genomes were found in apparently healthy pigs in the United States and Germany . In a recent similar study with serum samples from apparently healthy pigs, APPV prevalence reached from 2.3% to 17.5% in Europe and from 5% to 11% in China . All of the results demonstrated that APPV was highly prevalent in both apparently healthy pigs and CT‐affected pigs, suggesting the virus may have spread worldwide.…”
Section: Epidemiology and Transmissionmentioning
confidence: 76%
See 4 more Smart Citations
“…Moreover, it has been reported that detection rates of 2.4% to 22% for APPV genomes were found in apparently healthy pigs in the United States and Germany . In a recent similar study with serum samples from apparently healthy pigs, APPV prevalence reached from 2.3% to 17.5% in Europe and from 5% to 11% in China . All of the results demonstrated that APPV was highly prevalent in both apparently healthy pigs and CT‐affected pigs, suggesting the virus may have spread worldwide.…”
Section: Epidemiology and Transmissionmentioning
confidence: 76%
“…5,16,20 In a recent similar study with serum samples from apparently healthy pigs, APPV prevalence reached from 2.3% to 17.5% in Europe and from 5% to 11% in China. 21 All of the results demonstrated that APPV was highly prevalent in both apparently healthy pigs and CT-affected pigs, suggesting the virus may have spread worldwide. A most recent finding shows that presence of APPV genome in the serum samples of wild boars in Germany reached 19%, suggesting that the wild boars may be an important APPV reservoir.…”
Section: Epidemiology and Transmissionmentioning
confidence: 88%
See 3 more Smart Citations